Effectiveness of Brainstorming-Balanced Health Education in Improving Nutritional Diets in Stunted Toddlers - Daratullaila Daratullaila; Agrina Agrina; Erika Erika (GLOBAL HEALTH SCIENCE GROUP, 2026)
Stunting is a chronic nutritional problem that affects children's growth and development due to eating patterns that do not align with balanced nutrition. Mothers, as primary caregivers, play a crucial role, so effective and participatory nursing interventions are essential. This study used Dorothy E. Johnson's Behavioural System Theory as an environmental stimulus that influences behavioural systems. The objective of this study was to analyse the effect of health education using the brainstorming method on balanced nutritional eating patterns in stunted toddlers. This study used a quasi-experimental design with a one-group pretest-post-test approach. The health education intervention was conducted over three weeks through three stages. The Round Robin brainstorming method was used. The study sample consisted of 38 mothers of stunted toddlers, selected using purposive sampling. The measurement tool employed the Food Frequency Questionnaire (FFQ), which underwent validity and reliability tests, showing good content validity and an acceptable reliability coefficient (Cronbach’s alpha = 0.8). The research showed that the majority of children's eating patterns before the brainstorming method were in the poor category (76.3%), and after the intervention, 63.2% of toddlers' eating patterns were in the good category. The Wilcoxon test results indicated a significant effect of health education using the brainstorming method on changes in the dietary patterns of stunted toddlers. Health education using the brainstorming method had a significant effect on improving balanced nutrition in stunted toddlers.